Crosstalk between Nutrition, Insulin, Juvenile Hormone, and Ecdysteroid Signaling in the Classical Insect Model, Rhodnius prolixus - Leyria, Jimena; Benrabaa, Samiha; Nouzova, Marcela; Noriega, Fernando G; Tose, Lilian Valadares; Fernandez-Lima, Francisco; Orchard, Ian; Lange, Angela B (International journal of molecular sciences, 2022)
The rigorous balance of endocrine signals that control insect reproductive physiology is crucial for the success of egg production. Rhodnius prolixus, a blood-feeding insect and main vector of Chagas disease, has been used over the last century as a model to unravel aspects of insect metabolism and physiology. Our recent work has shown that nutrition, insulin signaling, and two main types of insect lipophilic hormones, juvenile hormone (JH) and ecdysteroids, are essential for successful reproduction in R. prolixus; however, the interplay behind these endocrine signals has not been established. We used a combination of hormone treatments, gene expression analyses, hormone measurements, and ex vivo experiments using the corpus allatum or the ovary, to investigate how the interaction of these endocrine signals might define the hormone environment for egg production. The results show that after a blood meal, circulating JH levels increase, a process mainly driven through insulin and allatoregulatory neuropeptides. In turn, JH feeds back to provide some control over its own biosynthesis by regulating the expression of critical biosynthetic enzymes in the corpus allatum. Interestingly, insulin also stimulates the synthesis and release of ecdysteroids from the ovary. This study highlights the complex network of endocrine signals that, together, coordinate a successful reproductive cycle.
Keywords: Animals; Ecdysteroids; Female; ekdysteroidy; Juvenile Hormones; corpus allatum; ženské pohlaví; hormone titers; insect; endocrine signaling; Insulin, Regular, Human; hmyzí hormony; Insulin; ovary; Insect Hormones; Rhodnius; juvenilní hormony; zvířata; inzulin; inzulin lidský